Cardiorespiratory Fitness and Risk of Incident Atrial Fibrillation. Issue 21 (26th May 2015) - Qureshi, Waqas T.; Alirhayim, Zaid; Blaha, Michael J.; Juraschek, Stephen P.; Keteyian, Steven J.; Brawner, Clinton A.; Al-Mallah, Mouaz H.
<x xml:space="preserve">Abstract</x> Background— Poor cardiorespiratory fitness (CRF) is an independent risk factor for cardiovascular morbidity and mortality. However, the relationship between CRF and atrial fibrillation (AF) is less clear. The aim of this analysis was to investigate the association between CRF and incident AF in a large, multiracial cohort that underwent graded exercise treadmill testing. Methods and Results— From 1991 to 2009, a total of 64 561 adults (mean age, 54.5±12.7 years; 46% female; 64% white) without AF underwent exercise treadmill testing at a tertiary care center. Baseline demographic and clinical variables were collected. Incident AF was ascertained by use of International Classification of Diseases, Ninth Revision code 427.31 and confirmed by linkage to medical claim files. Nested, multivariable Cox proportional hazards models were used to estimate the independent association of CRF with incident AF. During a median follow-up of 5.4 years (interquartile range, 3–9 years), 4616 new cases of AF were diagnosed. After adjustment for potential confounders, 1 higher metabolic equivalent achieved during treadmill testing was associated with a 7% lower risk of incident AF (hazard ratio, 0.93; 95% confidence interval, 0.92–0.94; P<0.001). This relationship remained significant after adjustment for incident coronary artery disease (hazard ratio, 0.92; 95% confidence interval, 0.91–0.93; P<0.001). The magnitude of the inverse association between CRF and incident AF was greater among obese compared with nonobese individuals (P for interaction=0.02). Conclusions— There is a graded, inverse relationship between cardiorespiratory fitness and incident AF, especially among obese patients. Future studies should examine whether changes in fitness increase or decrease risk of atrial fibrillation. This association was stronger for obese compared with nonobese, especially among obese patients.